A Meta-Analysis of Online Learning Practices Emerged During The Covid 19 Pandemic: Sebuah Meta Analisis Tentang Praktik Pembelajaran Online di Masa Pandemi Covid 19 - Alfiriani, Adlia; Rini, Faiza; Darman, Regina Ade; Rindaningsih, Ida (Universitas Muhammadiyah Sidoarjo, 2024)
The purpose of this paper was to explore and summarize the emerging pedagogical practices in online learning during the pandemic period, namely from 2019 to 2021. A meta-analysis of related studies was carried out in this study. The study was obtained from the Google Scholar and Scopus databases using online learning during the COVID-19 pandemic. 500 studies were identified, then analyzed to match the criteria set out for this study. Only five studies fulfilled these criteria and were thus selected for the study. The four studies included in this review emphasize different pedagogical practices of online learning and repost their impact on academic outcomes. Four studies were quantitative, while one was developmental. The pedagogical practices are flipped classroom, augmented reality, problem-based learning, and project-based learning. Furthermore, how this pedagogy is applied in an online learning environment is also presented in the research results section. This paper is original and very useful for educators/instructors because it can be the basis for developing effective online learning designs for students in the new normal era.